BATAS-BATAS KEMAMPUAN HUKUM DALAM MENGHADAPI PERUBAHAN SOSIAL - Eman Sulaeman (Jurnal Hukum Islam, 2014)
Law is a tool to manage the social life, either as social control or as social engineering. But there is a problem: thelaw exactly almost always left behind of the objects that is regulated. So, there will be always gap between law and social behavior, either significant or not. This problem will be serious if the gap between formal regulation and social reality that happened has passed over the normal boundaries, in which the fact of law has fallen behind from the social reality has been too significant, but there is no realization of the adjusments that should have been done. At that time the huge gaps happens and so do the strained situation between social changing and the law that regulates it. This writing tried to explain how the ability of law to adjust with the social changing.